Analisis Layanan Lembaga Publik terhadap Kepuasan Masyarakat di Kota Semarang - Sasana, Hadi (Jurnal Ilmu Ekonomi ASET, 2010)
Local governments must provide good public services, in an era of regionalautonomy and fiscal decentralization.This study aimed to analyze the quality of public servicesto the satisfaction of the people in the city of Semarang. Analysis tool used Stuctural EquationModeling (SEM).The results showed responsiveness and emphaty public sector had positiveand significant impact on peopleâs satisfaction in the City of Semarang.Keywords: tangibles, reliability, assurance, responsiveness, emphaty.